2013
DOI: 10.20870/oeno-one.2013.47.3.1552
|View full text |Cite
|
Sign up to set email alerts
|

A new method of protein extraction from red wines

Abstract: <p style="text-align: justify;"><strong>Aim</strong>: Wine is a very complex medium and is often evaluated according to its main components like alcohol, sugar, tannins, and acid levels. Proteins are rarely considered in this evaluation because their concentrations are only a few mg/L of wine. However, in an enological context, proteins appear to be more and more important, in particular for the stability of wines with protein haze problems. The study of proteins is less obvious in red wines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…To our knowledge, the work on non- vinfera grape varieties, and some vinifera varieties, was the first to quantify this effect in red wines . On the other hand, various studies have reported the presence of protein in soluble complexes with PA , and in the case of Shiraz (Syrah) proteins corresponding to the molecular weight of PR-proteins are notably absent . Together with our results, these observations provide evidence that a fraction of PA is likely to be removed from vinifera red wines and that this effect is quantitatively much smaller compared to certain non- vinifera varieties, which contain naturally high levels of PR-proteins .…”
Section: Results and Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…To our knowledge, the work on non- vinfera grape varieties, and some vinifera varieties, was the first to quantify this effect in red wines . On the other hand, various studies have reported the presence of protein in soluble complexes with PA , and in the case of Shiraz (Syrah) proteins corresponding to the molecular weight of PR-proteins are notably absent . Together with our results, these observations provide evidence that a fraction of PA is likely to be removed from vinifera red wines and that this effect is quantitatively much smaller compared to certain non- vinifera varieties, which contain naturally high levels of PR-proteins .…”
Section: Results and Discussionsupporting
confidence: 77%
“…A natural conclusion from their study, and the data presented here is that albeit at far lower protein concentrations, red vinifera varieties may resent PA losses via precipitation with proteins during crushing and winemaking. This also might account for the generally low levels of grape-derived PR protein recovered in finished red vinifera wines, which for Shiraz in particular are <2 μg/mL . The potential for grape-derived proteins to fine PA during the winemaking and aging process has been suggested historically, , but studies confirming that the phenomenon exists in vinifera red grapes and wines are lacking.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Protein quantification was performed using a UV-visible spectrophotometer (BioDrop µLite, from Thermo Fisher Scientific, Waltham, MA, USA) for micro sample volumes. For measurement and quantification, all of the protein powder extracted from 16 mL of wine sample according to the preparation described by Silvestri et al [14] was used. Thus, 40 µL of 0.16 M TRIS-HCL (pH 6.8) was added to the protein powder in a 1.5 mL tube and then placed in an ultrasound bath for 60 min at 50 • C. The measurement of the absorbance of the proteins was carried out at 280 nm using 3 µL of sample.…”
Section: Protein Analysis 231 Total Protein Concentration Determined By Uv Spectrophotometric Methodsmentioning
confidence: 99%
“…Samples of base wines were analyzed by means of sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) (Figure S1). A previous sample extraction treatment was carried out, which was used both for its quantification by UV and for gel electrophoresis, as described by Silvestri et al [14]. The proteins of the extracted wine samples were separated using SDS-PAGE (15% resolving gel and 5% stacking gel) in a vertical electrophoresis unit with an applied voltage of 100 V. The marker used was Precision Plus Protein™ Dual color Standards (Bio-Rad, Hercules, CA, USA).…”
Section: Wine Protein Composition Evaluated By Sds-pagementioning
confidence: 99%